Evaluasi dan Perancangan Sistem Pengendalian Internal Penerimaan Dana ZISWAF Menggunakan Kerangka COSO Pada Yayasan X - Fadhlan Ghani Padmanegara; Sugih Sutrisno Putra (Indonesian Accounting Literacy Journal, 2026)
The management of ZISWAF fund receipts at Foundation X faces challenges arising from multiple receipt accounts, manual data exchange through Excel and OneDrive, and unintegrated information systems. This study aims to evaluate and design an improved internal control system for ZISWAF fund receipts. A qualitative descriptive approach was employed through participatory observation, semi-structured interviews, and documentation. The evaluation applied the COSO framework and a control matrix to identify existing and missing controls. The results show that internal control has generally been implemented effectively; however, improvements are required in procedure standardization, monitoring follow-up documentation, and information system integration. Theoretically, this study contributes to the application of the COSO framework combined with a control matrix in evaluating and designing internal controls for ZISWAF fund receipts. This study is limited to one organization and the fund receipt process. The proposed design is expected to improve effectiveness, efficiency, coordination, and information reliability.